ANALISIS PERILAKU PEMBERIAN VAKSINASI COVID-19 PADA ANAK USIA 6-11 TAHUN DI SEKOLAH DASAR NEGERI 03 CEMPAKA PUTIH JAKARTA TIMUR TAHUN 2021 - Citya Indra Yarman; Wapada Wapada; Sri Rahayu (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
The Covid-19 pandemic has resulted in a significant increase in illness and mortality, discruping the global community’s social order. Many studies have concentrated on producing vaccine for children aged 6-11 years old in order to promote the optimization of teaching and learning activities in schools and to protect children agains from Covid-19 exposure. This study employs a case study methodology and employ a qualitative research method (case study). Collecting data in this study with Focus Group Discussion (FDG) and indepth interviews. The study carried out state elementary school 03 Cempaka Putih in East Jakarta, using a purposive sample approach mothers whose children were vaccinated, school principals, UKS persons in charge, persons in charge vaccination program, and vaccination officer from puskesmas. There results showed that the implementation of vaccination activities went smoothly. It hope that the health workers can increase socialization with the Covid-19 vaccination of children to communities.